Application of deferred taxes in accordance with the financial accounting system under the Algerian tax system - ikhlef, randa ibtissame (Journal of Research in Finance and Accounting, 2021)
This study aimed to introduce deferred taxes resulting from temporary differences between the Algerian tax system and the financial accounting system to gain a clear picture of dealing with this accounting problem. It was concluded through the study that the application of deferred taxes or not affects the outcome of the fiscal year, making it an approved method that gives credibility and transparency to financial statements, which contributes to rational investment decisions, but the lack of training and training courses in this area has led to their failure to be applied by the majority of accounting professionals.